Effectiveness of Simulation-Based Training on Pediatric Advanced Life Support (PALS) Knowledge and Skills among B.Sc. Nursing Students - Sharma, Vimala (Academia Research Journal, 2025)
Pediatric emergencies, particularly respiratory failure and shock, are leading causes of cardiopulmonary arrest in children and require rapid, skilled intervention. Pediatric Advanced Life Support (PALS) training equips healthcare providers with the knowledge and skills necessary for effective pediatric resuscitation. This study evaluated the effectiveness of simulation-based PALS training on the knowledge and skills of B.Sc. Nursing fourth-year students in Moradabad, Uttar Pradesh. A quantitative pre-test/post-test control group design was employed, involving 80 participants equally divided into experimental and control groups. The experimental group underwent three days of simulation-based PALS training, while the control group received no intervention during the study period. Data were collected using a demographic questionnaire, a 26-item knowledge questionnaire, and a 25-item skills checklist, with established validity and high reliability (knowledge tool α = 0.89, skills checklist α = 0.97). Results showed a significant improvement in the experimental group’s mean knowledge score from 7.15 to 15.50 (p < 0.001) and mean skills score from 3.20 to 20.78 (p < 0.001), whereas the control group showed no significant changes. Post-test comparisons revealed the experimental group outperformed the control group in both knowledge (mean difference = 6.65) and skills (mean difference = 16.03) at p < 0.001. No demographic variables were significantly associated with knowledge scores, though parents’ education was significantly related to skills scores. The findings confirm that simulation-based PALS training is highly effective in enhancing both cognitive and psychomotor competencies in nursing students, supporting its integration into undergraduate nursing curricula to improve preparedness for pediatric emergencies.